THE BATTLE OF CHAERONEA: 86 BCE - Belfiglio, Valentine J. (International Journal of Research -GRANTHAALAYAH, 2024)
In 86 BCE Proconsul Lucius Cornelius Sulla’s (138-78 BCE) looked over the potential battlefield at the broad plain near Chaeronea. He heard horses neigh, and men rumble as they set up camp. Sulla knew the upcoming engagement of his 30,000 legionnaires against the 120,000-man army of Mithridates VI (135-78 BCE) (Appian 12.3.17, 12.6.41) of Pontus would be bloody, brutal, and deadly. General Archelaus commanded the Pontic forces. Sulla may have reflected on the cascade of events which placed him in this dire situation. In 107 BCE. Consul Gaius Marius (157-86 BCE) initiated policies designed to enhance the efficacy of the Roman army. One of these reforms placed the responsibility to supply and manage an army under the authority of the commanding general, rather than the Consul and Senate. This change allowed charismatic, ambitious generals to divert the primary loyalty of soldiers to themselves rather than the State. Sulla used this change in loyalty to march on Rome in 88 BCE and 82 BCE. (Plutarch 2.3.1) In 89 BCE Mithridates embarked on a policy of military expansionism. He invaded Bithynia and Cappadocia, even though Roman officials warned him to respect Bithynia’s sovereignty. The Roman Senate declared war on Pontus, appointed Sulla to prosecute the war, and the First Mithridatic War began (89-84 BCE). (Appian 12.4.22, 12.5.30) Mithridates’ army overran Roman provinces in Asia Minor. Cassius Dio reported: “All the Asiatic, at the bidding of Mithridates massacred the Romans.” (Dio 31.101) Mithridates then invaded the Roman province of Greece. The seizure of Roman territory and murder of Roman citizens was a grievous affront to the honor of Senatus Populusque Romanus (the Senate and People of Rome). Mithridates must have known from the history of Carthage what fate awaited him and Pontus if his military adventurism failed. Either he must destroy the Roman Republic, or it would destroy Pontus and humiliate, then kill him. Control over the region of the Eastern Mediterranean was at stake. Civil War diverted Sulla’s attention, but he finally advanced against Pontic armies in Greece in 87 BCE. He quickly drove two Mithridatic armies into the fortifications of Athens and the Piraeus. Then he successfully moved against these two fortifications. Archelaus escaped by sea to Boeotia. Sulla followed him with his army to Chaeronea, in central Greece. He had Legates Sulpicious Galba, Licinious Murena, and Lucius Hortensius under his command (Plutarch 15.17).